Development of image-guided puncture robot used in trigeminal neuralgia treatment. (19th November 2021) - Liu, Bin; Yang, Hongbo; Guo, Kai; Luo, Caijun; Liu, Chang; Zhang, Senhao; Zhang, Yingying; Li, Zhenlan
Recently, invasive surgery had developed rapidly and was widely used in the fields of tumour treatment, spine and joint disease treatment. At present, most of the analgesic puncture operations were performed manually by doctors in the CT environment. High skills are required during such complex surgery; it also increases the doctors' risk due to exposure to the radiation environment. This paper studies image-guided puncture robots. In this work, through the use of binocular vision cameras, real-time medical image data was collected during the surgery using CT. Also, we setup the model for the spatial solution of the manipulator and integrated with the image data, to make a set of graphical operation interface. Under the guidance of the doctors, the posture of the manipulator was controlled to achieve the specific position required by the doctors. Through the development of software, hardware and algorithm, we designed and developed an image-guided, minimally invasive surgical real-time robotic system to improve the safety and accuracy of the surgeon during the puncture procedure.